2017
DOI: 10.1186/s40663-017-0107-x
|View full text |Cite
|
Sign up to set email alerts
|

Tree water potentials supporting an explanation for the occurrence of Vachellia erioloba in the Namib Desert (Namibia)

Abstract: Background: Site-vegetation relations of Vachellia erioloba, Faidherbia albida, Euclea pseudebenus and Tamarix usneoides in two contrasting locations in the Namib Desert (Namibia) were evaluated with the goal to relate soil water availability to the occurrence of trees under hyper-arid conditions. Methods: Plant water potentials were measured using a pressure chamber in the field. Pre-dawn water potentials were assessed to reflect the soil water potential of the rhizosphere. Midday water potentials were measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 30 publications
2
10
0
Order By: Relevance
“…For instance, Bhark and Small (2003) showed that water infiltration rarely exceeds half a meter after rainy periods in woody–grassy mosaics of New Mexico, while Yang et al (2012) also found a lack of deep soil recharge in arid forest-steppes of the Chinese Loess Plateau. Nevertheless, large sandy regions with sparse tree cover and good soil infiltration capacity, such as the Namibrand in South Africa (Krug 2017), the Keerqin area in NE China (Zeng et al 2009), the Nebraska Sand Hills in North America (Adane et al 2018) or the Doñana sand dunes in Spain (Munoz-Reinoso and Novo 2005) may show soil moisture patterns similar to our findings.…”
Section: Discussionsupporting
confidence: 84%
“…For instance, Bhark and Small (2003) showed that water infiltration rarely exceeds half a meter after rainy periods in woody–grassy mosaics of New Mexico, while Yang et al (2012) also found a lack of deep soil recharge in arid forest-steppes of the Chinese Loess Plateau. Nevertheless, large sandy regions with sparse tree cover and good soil infiltration capacity, such as the Namibrand in South Africa (Krug 2017), the Keerqin area in NE China (Zeng et al 2009), the Nebraska Sand Hills in North America (Adane et al 2018) or the Doñana sand dunes in Spain (Munoz-Reinoso and Novo 2005) may show soil moisture patterns similar to our findings.…”
Section: Discussionsupporting
confidence: 84%
“…For instance, Bhark and Small () showed that water infiltration rarely exceeds half a meter after rainy periods in woody–grassy mosaics of New Mexico, while Yang et al () also found a lack of deep soil recharge in arid forest‐steppes of the Chinese Loess Plateau. Nevertheless, large sandy regions with sparse tree cover and good soil infiltration capacity, such as the Namibrand in South Africa (Krug ), the Keerqin area in NE China (Zeng et al ), the Nebraska Sand Hills in North America (Adane et al ) or the Doñana sand dunes in Spain (Munoz‐Reinoso and Novo ) may show soil moisture patterns similar to our findings.…”
Section: Discussionsupporting
confidence: 83%
“…Camelthorns are the largest trees in the Kalahari, growing up to 16 m tall (Krug 2017) with canopy diameters up to 22 m (Carr 1976, Moustakas et al . 2006).…”
Section: Figurementioning
confidence: 99%